THE IMPACT OF LIGHTNING STRIKE ON HYBRID HIGH VOLTAGE OVERHEAD TRANSMISSION LINE – INSULATED GAS LINE - Boumous, Samira; Boumous, Zouhir; Djeghader, Yacine (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
The electrical network is the set of elements where loads are connected to the generation plants by transmission lines. They can be either overhead or underground cables. A new technology has been introduced to replace these transmission lines with underground cables gas insulated line “GIL”. The latest has many advantages over underground cables and overhead transmission lines, such as low transmission losses, less capacitive load, reliability, personal safety, same operation as overhead lines and negligible electrical aging. GIL can handle much more power than overhead lines due to its large conductive area. GIL is the best for high voltage. In this paper, the simulation of lightning strike effects on a 400 kV hybrid transmission line located in the Wilaya of Setif in northern Algeria is presented in the absence and presence of line arresters and GIL arresters. The results of this paper can provide a rich and valuable theoretical reference for GIL simulation modeling and evaluation of lightning strike impact on hybrid overhead – GIL lines.